Absolwenci pedagogiki na rynku pracy. Losy zawodowe absolwentów Uniwersytetu Zielonogórskiego = Pedagogy Graduates on the Labour Market. Career History of University of Zielona Gora Graduates - Kołodziejska, Elżbieta; Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article will present the results of the research performed on chosen at random graduates of the Faculty of Education, Sociology and Health Sciences, University of Zielona Gora. It is important to say that the authors understand the concept of a graduate much broader than it is seen in the surveys run by GUS (Central Statistical Office) or employment offices. Research subjects are people who graduated from the University of Zielona Gora within the last five years.
Keywords: Uniwersytet Zielonogórski - Wydział Pedagogiki, Socjologii i Nauk o Zdrowiu; szkolnictwo wyższe; absolwenci; monitorowanie losów absolwentów